Polish Regulation Model of Civil Court Mediation and Assessment of Its Effectiveness - Mariusz Maciejewski (Krytyka Prawa)
The aim of the article is to present to international researchers the Polish model of legal regulation regarding civil court mediation. The second aim is to present an assessment of the effectiveness of these legal solutions. For these purposes, the article discusses said legal regulations and then follows up with a review of statistical data on the use of mediation in court proceedings. This leads to the assessment of the effectiveness of the presented legal model. The research concludes that despite the significant social need and the extensiveness of the legal regulation in force, the use of mediation in Poland remains at very low level and is not developing. Research shows that there are – not yet identified –reasons that hinder the development of mediation in Poland. Therefore, this article also aims to show which regulatory model does not work or, in other words, which regulatory model is not sufficient to develop civil court mediation in Poland – and maybe in other jurisdictions.